FORMULASI MODEL BERPIKIR KRITIS PEMBACA YANG “BIAS” TERHADAP TEKS BALIHO DI KOTA SERAMBI MEKAH: KAJIAN SEMIOTIK BUDAYA - Sulastri Sulastri; Diah Tyahaya Iman; Ronidin Ronidin (Puitika, 2019)
Padang Panjang can be considered as a heterogeneous city in the existence of a communal community. The city can position itself as a party that can explain the benchmarks of the critical attitudes of the reading community towards billboard texts. The thoughts of billboard readers can be transformed to a formulation model for the readers' critical attitude towards the billboard texts displayed on the roadsides. The readers' thoughts are perfunctory, inquisitive, curious, and their critical attitudes are influenced by a very complex city environment. Factors of education, religion, trade, intersection city (Ikua Darek, Head of Rantau) could be a practical barometer of politic. This study is aimed to answer what formulation model of the critical attitude of billboard texts readers in the city of the Veranda of Mecca is like and whether in Is the city full of complexity there is a possibility that ideology is seen as the cultural expressions both in verbal and communication form reflected on the billboard texts. This paper examines the meanings and how the myths of the Veranda of Mecca city in the cultural expressions are presented in the signs billboard texts.